Uncertainty analysis of velocity field calibration in wind tunnels based on GUM and MCM. Issue 1 (1st July 2022) - Du, Yufeng; Xiong, Neng; Lin, Jun
Abstract: The flow quality of wind tunnel is an important index to judge the performance of the wind tunnel, and it directly determines whether the aircraft can obtain high-quality test data, and directly relates to the ability of the wind tunnel to be applied to basic aerodynamic research. Velocity field calibration is necessary in flow field calibration and an important prerequisite for the accurate simulation of Mach number in wind tunnel tests. In this paper, the GUM method and the MCM method are used to compare and analyze the uncertainty of velocity field calibration of the high-speed wind tunnel, and the uncertainty of the Mach number in the range of 0.6 to 4 is solved. The uncertainty evaluation results of the two methods are basically the same, and are equivalent to the wind tunnel Mach number control accuracy value, which verifies the correctness of the evaluation results of the velocity field calibration uncertainty of high-speed wind tunnel, and the MCM method results verify the direct applicability of the GUM method for uncertainty evaluation in similar application scenarios.